LITERATUR REVIEW : HUBUNGAN SELF-EFFICACY DAN MINAT BELAJAR DALAM MENYELESAIKAN MASALAH MATEMATIS SISWA - Rika, Rika; Aisyah Nursyam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The ability to solve mathematical problems is an essential aspect of mathematics learning, influenced by affective factors such as self-efficacy and learning interest. This study aims to analyze the relationship between self-efficacy and learning interest in supporting students’ ability to solve mathematical problems. The method used is a systematic literature review of scientific articles published between 2022 and 2025, with searches conducted through Google Scholar, and SINTA using the keywords “self-efficacy,” “learning interest,” and “mathematical problem solving.” A review of 30 relevant articles shows that self-efficacy affects students’ confidence and perseverance, while learning interest enhances motivation and active engagement in the problem-solving process. Overall, both factors contribute positively to improving students’ mathematical problem-solving abilities.